Significance of thrombocytopenia in patients with primary and postessential thrombocythemia/polycythemia vera myelofibrosis. (17th January 2018) - Masarova, Lucia; Alhuraiji, Ahmad; Bose, Prithviraj; Daver, Naval; Pemmaraju, Naveen; Cortes, Jorge; Pierce, Sherry; Kantarjian, Hagop; Verstovsek, Srdan
Abstract: Severe thrombocytopenia (platelets <50 × 10 9 /L) is associated with very poor outcome of patients with myelofibrosis (MF). As patients with primary myelofibrosis (PMF) differ from patients with postessential thrombocythemia (PET‐MF) and postpolycythemia vera myelofibrosis (PPV‐MF), we aimed to evaluate the significance of low platelets among these patients. We present clinical characteristics and outcome of patients with either PMF, PPV‐MF, or PET‐MF, and thrombocytopenia who presented to our institution between 1984 and 2015. Of 1269 patients (877 PMF, 212 PPV‐MF, 180 PET‐MF), 11% and 14% had platelets either <50 × 10 9 /L or between 50‐100 × 10 9 /L, respectively. Patients with platelets <50 × 10 9 /L were most anemic and transfusion dependent, had highest blast count and unfavorable karyotype. In general, their overall and leukemia‐free survival was the shortest with median time of 15 and 13 months, respectively; with incidence of acute leukemia almost twice as high as in the remaining patients (6.9 vs 3.6 cases per 100 person‐years). Nevertheless, this observation remains mostly significant for patients with PMF, as those with PEV/PVT‐MF have already significantly inferior prognosis with platelets <100 × 10 9 /L.